Inhibiting Histone and DNA Methylation Improves Cancer Vaccination in an Experimental Model of Melanoma - De Beck, Lien; Awad, Robin Maximilian; Basso, Veronica; Casares, Noelia; De Ridder, Kirsten; De Vlaeminck, Yannick; Gnata, Alessandra; Goyvaerts, Cleo; Lecocq, Quentin; San José-Enériz, Edurne; Verhulst, Stefaan; Maes, Ken; et al. (Frontiers in Immunology, 2022)
Immunotherapy has improved the treatment of malignant skin cancer of the melanoma type, yet overall clinical response rates remain low. To meet this cogent medical need, combination therapies could be key. Because epigenetic hallmarks represent promising combination therapy targets, we studied the immunogenic potential of a dual inhibitor of histone methyltransferase G9a and DNA methyltransferases (DNMTs) in the preclinical B16-OVA melanoma model. Making use of tumor transcriptomic and functional analyses, dual methylation-targeted epigenetic reprogramming was shown to induced tumor cell cycle arrest and apoptosis, coinciding with transient tumor growth delay in vivo and an IFN-I response in immune-competent mice. In vitro, the drug had no significant effects on dendritic cell maturation or T-cell activation. In vivo, dual epigenetic inhibition promoted dendritic cell and to a lesser extent T-cell infiltration yet failed to sensitize tumor cells to programmed cell death-1 inhibition. Instead, it increased therapeutic efficacy of TCR-redirected T cell and dendritic cell vaccination, jointly increasing overall survival of B16-OVA tumor-bearing mice. The reported data confirm the prospect of methylation-targeted epigenetic reprogramming in melanoma and sustain dual G9a and DNMT inhibition as a strategy to tip the cancer-immune set-point balance towards responsiveness to active and adoptive vaccination against melanoma.